2022
DOI: 10.1021/acsami.2c14433
|View full text |Cite
|
Sign up to set email alerts
|

Combining Cobalt Ferrite Nanozymes with a Natural Enzyme to Reshape the Tumor Microenvironment for Boosted Cascade Enzyme-Like Activities

Abstract: Nanozymes with the merits of effective enzyme-mimic activities, tunable catalytic properties, pH/temperature tolerance, and high stability have been consumingly researched for nanocatalytic therapy. Herein, the union nanozymes and a natural enzyme nanoplatform (DMSN@CoFe 2 O 4 /GOD-PCM) are elaborately designed by simply depositing an ultrasmall cobalt ferrite (CoFe 2 O 4 ) bimetallic oxide nanozyme and natural glucose oxidase (GOD) that are loaded into the aperture (∼12 nm) of dendritic mesoporous silica (DMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…The in vitro and in vivo results indicated that the IrRu-GOx@PEG NPs could effectively induce 4T1 cell apoptosis. In addition, a nanoplatform (DMSN@CoFe 2 O 4 /GOD-PCM) was designed for NIR II-enhanced tumor therapy by depositing ultrasmall cobalt ferrite (CoFe 2 O 4 ) and GOx into the pore size of dendritic mesoporous silica ( Chang et al, 2022 ) ( Figure 6B ). After laser irradiation, the high temperature generated by CoFe 2 O 4 melts the phase change material (PCM) to release GOx, remodelling the TME through the glucose metabolism pathway.…”
Section: Nanomaterial-mediated Tumor Hypoxia Reliefmentioning
confidence: 99%
“…The in vitro and in vivo results indicated that the IrRu-GOx@PEG NPs could effectively induce 4T1 cell apoptosis. In addition, a nanoplatform (DMSN@CoFe 2 O 4 /GOD-PCM) was designed for NIR II-enhanced tumor therapy by depositing ultrasmall cobalt ferrite (CoFe 2 O 4 ) and GOx into the pore size of dendritic mesoporous silica ( Chang et al, 2022 ) ( Figure 6B ). After laser irradiation, the high temperature generated by CoFe 2 O 4 melts the phase change material (PCM) to release GOx, remodelling the TME through the glucose metabolism pathway.…”
Section: Nanomaterial-mediated Tumor Hypoxia Reliefmentioning
confidence: 99%
“…Chang and coworkers developed a nano-platform DCGP (DMSN@CoFe 2 O 4 /GOD-PCM) with a combination of nanozyme and natural enzyme, which was realized by the deposition of ultrasmall CoFe 2 O 4 bimetallic oxide and glucose oxidase (GOD) into the large mesopores of dendritic mesoporous silica (DMSN). 52 The cascade catalysis reactions of the CoFe 2 O 4 nanozymes were TME-activated. GOD strengthened the weak acidity of the tumor area and produced more H 2 O 2 .…”
Section: The Construction and Engineering Principles Of Current Nanoz...mentioning
confidence: 99%
“…As discussed in Figure 1G,H there are two redox couples (Fe 2+ /Fe 3+ and W 5+ /W 6+ ) in the prepared Fe-PTs, which can facilitate the regeneration of Fe 2+ by capturing electrons from the W 6+ species. 43,44 Moreover, the high surface electron density of polyoxotungstate clusters in Fe-PTs can also accelerate the reduction of Fe 3+ to Fe 2+ (Figure 2D). 45 The two pathways synergistically promote the decomposition of H 2 O 2 into hydroxyl radicals.…”
Section: ■ Introductionmentioning
confidence: 99%